2013
DOI: 10.4238/2013.october.24.12
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in natural populations of Theobroma subincanum Mart. in the Brazilian Amazon

Abstract: ABSTRACT. The genus Theobroma, recently reclassified in the family Malvaceae, comprises some species with high economic potential, including the cupuí, Theobroma subincanum Mart., which has not yet been domesticated, and whose genetics and population structure are mostly unknown. This study aimed to assess the population structure and genetic diversity in natural populations of T. subincanum Mart., using inter-simple sequence repeat (ISSR) markers. A total of 59 individuals were sampled in three geographically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 16 publications
2
12
0
4
Order By: Relevance
“…In the level of species, the genetic diversity was H=0,27 and I=0.41 (Table 2). Similar results were found by many works that studied native species from Amazon, such as Mauritia flexuosa (ROSSI et al, 2014), Theobroma subincanum (RIVAS et al, 2013) and Theobroma speciosum Willd. Ex Spreng (GIUSTINA et al, 2014).…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…In the level of species, the genetic diversity was H=0,27 and I=0.41 (Table 2). Similar results were found by many works that studied native species from Amazon, such as Mauritia flexuosa (ROSSI et al, 2014), Theobroma subincanum (RIVAS et al, 2013) and Theobroma speciosum Willd. Ex Spreng (GIUSTINA et al, 2014).…”
Section: Resultssupporting
confidence: 78%
“…Santana et al (2011), observed an average of 10 bands per primer when studied 17 accessions of umbu-cajazeiras belonging to BAG tropical fruit of Embrapa Mandioca e Fruticultura, based on ISSR markers. However, Rivas et al (2013), studied native populations of Theobroma subincanum Mart. and obtained results lower than those found in the present study, with the average number of bands per primer of 6,69.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, sapucaia is known to be a long-life tree species, and is preferably allogamous, its pollen is spread by bees and its seeds are spread by animals and humans (Mori and Prance, 1990). The results of some studies have shown that genetic distance does not always correlate with geographic distance (Rivas et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Inter-simple sequence repeats (ISSRs) are dominant and represent genetic variation within microsatellite regions in the genome. They have been used to estimate genetic diversity and genetic parameters of populations of multiple plant species (Rivas et al, 2013;Lorenzoni et al, 2014;Rossi et al, 2014;Silva et al, 2014;Ghariani et al, 2015;ArrigoniBlank et al, 2016;Shen et al, 2016). The advantage of ISSRs is the possibility to obtain a high number of polymorphic loci without the need of genome sequence knowledge (Faleiro, 2007).…”
Section: Introductionmentioning
confidence: 99%